(untitled) (Journal of the College of Basic Education, 2022)
The research deals with the study of the design objectives of the costume in the children’s theater as one of the elements of the theatrical performance, because it occupies a physical space on the stage, and at the same time it contributes to conveying the meaning and connotations to the child.